Polemic of Religious Intolerance among Indonesian Users on YouTube - Nur Aida Kubangun; Muhammad Tarmizi Kubangun; Aksa Noya (Faculty of Social and Political Sciences - UIN Walisongo Semarang, 2025)
Digital space has now become a medium for contestation and competition, including in the field of religion, in the context of Indonesia's multireligious society. YouTube is one of the social media that has become a digital space that can give rise to polemics of intolerance in religious harmony in Indonesia. The aim of this study is to find out the polemic of religious intolerance on YouTube channels. Using qualitative methods and a netnographic approach, data collection was carried out using YouTube media with content that is in accordance with the orientation of this study, namely the polemic of religious intolerance. The results show that there are 15 YouTube channels that upload 20 video contents about religious debates, responses to the uploaded videos show various comments from netizens who claim the truth of their respective religions. The implications of claims regarding religious truth often manifest in intolerance, conflict, hatred, and even war. This study is expected to contribute to the prevention of religious intolerance and support religious moderation in order to achieve a more harmonious and tolerant religious life.